HUBUNGAN ANTARA TINGKAT HASIL DI BURSA EFEK JAKARTA DENGAN TINGKAT HASIL BERBAGAI PASAR MODAL INTERNASIONAL DITINJAU DARI SUDUT PANDANG PEMODAL INDONESIA PERIODE 1998-1999 - Paulus Denny; Endang Ernawati (Journal of Management and Business, 2003)
Several studies in international investment give understanding about chance to invest in others countries. This article purposes to descript another investment opportunity for Indonesian investor in international area. The sample including Jakarta Stock Exchange (JSX), Strait Times Singapore (STS), Nikkei 225 Japan (Nikkei), Dow Jones Industrial Average USA (DJIA), dan Financial Times Stock Exchange (FTSE) 100 London. Data sets are weekly market return for years 1998 through 1999 periode.The result showed that in sample periode, JSX market returns have negatif relation or very little relation with others markets. Its means investors have chance to diversify their investment portfolio in international area.